1964
DOI: 10.1128/jb.87.3.588-592.1964
|View full text |Cite
|
Sign up to set email alerts
|

STORAGE OF MYCOPLASMA STRAINS

Abstract: Kelton, William H. (National Animal Disease Laboratory, Ames, Iowa). Storage of Mycoplasma strains. J. Bacteriol. 87: 588–592. 1964.—Survival of Mycoplasma strains (19 of avian origin, 3 human, 3 canine, and 1 saprophyte) in the lyophilized state and at various storage temperatures was studied. The effect of alternate freezing and thawing was also studied. All strains survived the freeze-drying process and at least 3 or 4 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The ability to recover viable mycoplasmas from frozen cultures makes possible the preservation of stock cultures by frozen storage and the provision of readily available standard inocula for physiological studies (1,5,6,14). Yet, until now no detailed investigation has been made of the factors affecting the survival of mycoplasmas during the freezing process and the following storage in the frozen state.…”
mentioning
confidence: 99%
“…The ability to recover viable mycoplasmas from frozen cultures makes possible the preservation of stock cultures by frozen storage and the provision of readily available standard inocula for physiological studies (1,5,6,14). Yet, until now no detailed investigation has been made of the factors affecting the survival of mycoplasmas during the freezing process and the following storage in the frozen state.…”
mentioning
confidence: 99%
“…With respect to the two temperature ranges that were used, there was no marked variation, favoring the viability of Mycoplasma fermentans P140 and PG18 during the twelve months of the test, evidencing by means of the culture in SP4 agar with a characteristic colonial growth of mycoplasmas with considerable diameters and abundant growth, as was the case with Mycoplasma fermentans P140 ( Figure 2 panel A and B) and Mycoplasma fermentans PG18 (Figure 2 panel D). Regarding the effect on the variation in the colonial growth of Mycoplasma fermentans P140 and PG18, this behavior is related to the absence of cell wall that characterizes mycoplasmas, an effect that has been reported in other work (Kelton, 1964) and given the diversity intraspecific of the microorganisms, it has been established that not all strains of the same species respond equally to the selection of tests applied to them (24,25).…”
Section: The Variations Obtained In the Viability Betweenmentioning
confidence: 75%
“…It has been reported that variations in conservation temperature and that the freezing and thawing process induce changes in the growth and size of mycoplasma colonies (8). An investigation evaluated the viability of mycoplasma cultures of animal origin during periods of two years at different freezing temperatures and in the lyophilized phase, finding that their viability was favored, but involved more infrastructure and high operating costs, highlighting that there are various reports that study the protocols to maintain the viability of mycoplasmas, the frequently described species being of veterinary interest (9-12).…”
Section: Introductionmentioning
confidence: 99%
“…Little work has been done in examining the viability of mycoplasma species. In observing avian, human, canine, and saprophytic types of mycoplasma, Kelton (1964) found considerable variation between strains in Original milk sample collected from cows at weekly intervals. A sample was collected from each mammary quarter and a composite sample was collected.…”
Section: Introductionmentioning
confidence: 99%